2001
DOI: 10.1002/j.1556-6676.2001.tb01954.x
|View full text |Cite
|
Sign up to set email alerts
|

The Physical Environment and Counseling: A Review of Theory and Research

Abstract: This article provides a review of published, counseling‐relevant literature on the physical environment, with a focus on physical elements that may enhance or detract from the counseling process. Specifically, it describes environmental variables that are relevant to counseling, providing examples of their practical importance, and in several cases describes possible application to counseling settings. Finally, this article identifies research implications and proposes a 3‐part future research agenda.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
84
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(93 citation statements)
references
References 83 publications
2
84
1
2
Order By: Relevance
“…On a proofreading task, employees made significantly more errors when they were in a room with white walls I compared to a room with blue or red walls. Pressly and Heesacker (2001) also propose that room color affects occupant behavior, but they also seem to suggest the importance of color in making an environment seem more social. In their review of counseling literature, they point out that different room colors can accentuate patient extroversion or introversion and can also affect how warm patients feel in a room.…”
Section: Studying Social Influence In Virtual Environmentsmentioning
confidence: 98%
See 1 more Smart Citation
“…On a proofreading task, employees made significantly more errors when they were in a room with white walls I compared to a room with blue or red walls. Pressly and Heesacker (2001) also propose that room color affects occupant behavior, but they also seem to suggest the importance of color in making an environment seem more social. In their review of counseling literature, they point out that different room colors can accentuate patient extroversion or introversion and can also affect how warm patients feel in a room.…”
Section: Studying Social Influence In Virtual Environmentsmentioning
confidence: 98%
“…Therefore, when trying to create a social environment, I propose that light wall colors should be used. In addition to wall color, Pressly and Heesacker (2001) point out that including textures in a room helps convey a message of comfort and intimacy to room occupants.…”
Section: Studying Social Influence In Virtual Environmentsmentioning
confidence: 99%
“…Evidence suggests that the colour of a room can augment some personality traits, elicit feelings of anger or comfort, and stimulate physiological responses (Dijkstra, Pieterse, & Pruyn, 2008;Korzh & Safuanova, 1993;Liu, 2014;Venolia, 1988). Pressly and Heesacker (2001) suggest that "warm hues and high intensities provide visual activation and stimulation, [whereas] cool hues and low intensities communicate subtlety and relaxation" (p. 150). According to Liu et al (2014), blue and green are the preferred colours and rooms of these colours tend to decrease the blood pressure, pulse and respiration of occupants.…”
mentioning
confidence: 99%
“…There is also some evidence to suggest that aspects of a room's décor (e.g. plants and artwork) can have an impact on its occupant's state of mind (McLeod & Machin, 1998;Miwa & Hanyu, 2006;Pressly & Heesacker, 2001), whereas Baack (2015) found that for genetic counselling the room set-up and décor did not have a significant impact on experiences of anxiety.…”
mentioning
confidence: 99%
See 1 more Smart Citation